Development Of Nutrition Application Prototype (REGIZI) As A Stunting Control Strategy - Asia, Siti Nur; Faisal, Faisal (SEAN Institute, 2024)
This first phase of research aims to develop and test a prototype of a nutrition application called Regizi as a stunting prevention strategy. This application is designed to provide nutrition education features, nutritional status monitoring, and online consultations aimed specifically at parents and caregivers of children under five. App development is carried out through a user-centered design approach, which involves the stages of need identification, design, and application development. The results of the initial trial show that Regizi is effective in increasing users' understanding of the importance of nutrition in stunting prevention and facilitating regular monitoring of children's nutritional status. Thus, Regizi has great potential as a tool in efforts to combat stunting, especially in rural areas that have limited access to health services. The wider implementation of this application, accompanied by improvements based on the results of further evaluation, is expected to make a significant contribution to reducing stunting rates in Indonesia.